Efficacy of Anti-PD1 Blockade in Treating Recurrent or Metastatic Nasopharyngeal Cancer: A Systematic Review and Meta-analysis. (January 2023) - Yeo, Brian Sheng Yep; Song, Harris Jun Jie Muhammad Danial; Soong, Yoke Lim; Chua, Melvin Lee Kiang; Ang, Mei-Kim; Lim, Darren Wan Teck; See, Anna; Lim, Chwee Ming
Highlights: Anti-PD1 antibodies demonstrate considerable activity in previously treated RM-NPC. Response rate increases when combined with Gemcitabine and Cisplatin. Future studies should investigate potential biomarkers and combinational therapies. Abstract: Objectives: Anti-PD1 antibody has emerged as a promising immunotherapeutic option in patients with recurrent and/or metastatic nasopharyngeal cancers (RM-NPC). We aim to summarise existing evidence on the use of anti-PD1 antibodies in the treatment of these patients and compare its effectiveness with standard-of-care palliative chemotherapy. Our secondary aim is to explore potential combination therapies with anti-PD1 antibodies. Materials and Methods: PubMed, Embase and Cochrane databases were systematically searched for studies comparing the efficacy of various anti-PD1 antibodies in the treatment of RM-NPC (either as first or second line treatment) from inception to 2 September 2022. Meta-analyses were performed to correlate the various anti-PD1 antibodies with primary endpoints including overall response rate disease control rate (DCR), progression free survival (PFS) and overall survival (OS). Results: Eighteen studies with 1, 887 patients met the inclusion criteria. The use of anti-PD1 antibody monotherapy as second-line treatment of RM-NPC revealed an ORR of 23 % (95 % CI = 19 %-28 %) and DCR of 51 % (95 % CI = 42 %-60 %). The ORRs for first-line as well as a combination of first and second-line treatments were 21 % (95 % CI = 15 % − 30 %) and 22 % (95 % CI = 6 % − 56 %, I 2 = 75 %) respectively. The 12-month PFS and 12-month OS was also 27 % (95 % CI = 21 %–33 %) and 63 % (95 % CI = 53 %-72 %) respectively. ORR was much higher at 73 % (95 % CI = 32 %-94 %) when anti-PD1 antibodies were combined with Gemcitabine plus Cisplatin. Conclusion: Anti-PD1 antibody demonstrate considerable activity in previously treated RM-NPC patients. Combining anti-PD1 antibodies with gemcitabine and cisplatin chemotherapy enhanced the efficacy of treatment.